Rumah.com: The Impact of Convenience, Brand Image, and Trust Towards Purchase Intention - Della Notonagoro; Innocentius Bernarto (Enrichment : Journal of Management, 2021)
The purpose of this study is to explore the factors of Convenience, Brand Image and Trustt towards customer’s online purchase intention through Rumah.com’s website. A sample of 195 individuals residing within the Jabodetabek region of Indonesia participated in this empirical study. This study utilized questionnaires as the main data gathering instrument and a non-probability convenience sampling. A multivariate analysis method of Partiall Least Square-Structural Equation Modeling (PLS-SEM) was used to validate the measurement model as well as to test the relationships in the structural model. Results revealed that Trust and Brand Image have more influence in online Purchase Intention, whereas Convenience was not proven to be significantly influential. The outcome in this study suggests that when it comes to luxury purchases as with the case of property buying, customers are more concerned with the perception of Trust and Brand Image of the company, therefore monitoring a positive brand image and maintaining the trust of customers by consistently meeting expectations is a prerequisite to achieving a higher Purchase Intention among customers.